Palygorskite changes heavy metal bioavailability and microbial functional diversity in sewage sludge composting - Liu, Siying (Environmental technology, 2015)
To investigate the effects of palygorskite on chemical forms of heavy metal and microbial functional diversity in the sewage sludge composting, a compost matrix of sewage sludge, wheat straw and varying contents of palygorskite were inoculated with the compound microbial preparation. The chemical speciation analysis by a Community Bureau of Reference-sequential extraction indicated the contribution of palygorskite to reduce the bioavailability of a model metal, Cu, during the composting process. The Biolog EcoPlate(TM) test revealed that the microbial community showed better capability of utilizing complex macro-molecules (such as miscellaneous and polymers) in the presence of palygorskite. Increasing the palygorskite contents from 1% to 5%, the microbial activity showed an increasing tendency. However, continuously increasing the palygorskite resulted in a decline of the microbial metabolism. Therefore, appropriate content of palygorskite is an ideal additive for composting, not only enhancing the microbial activity, but also reducing the metal toxicity